2016
DOI: 10.1002/2016ja022530
|View full text |Cite
|
Sign up to set email alerts
|

The local dayside reconnection rate for oblique interplanetary magnetic fields

Abstract: We present an analysis of local properties of magnetic reconnection at the dayside magnetopause for various interplanetary magnetic field (IMF) orientations in global magnetospheric simulations. This has heretofore not been practical because it is difficult to locate where reconnection occurs for oblique IMF, but new techniques make this possible. The approach is to identify magnetic separators, the curves separating four regions of differing magnetic topology, which map the reconnection X line. The electric f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
(106 reference statements)
2
12
0
Order By: Relevance
“…For the inflow speed, it has been shown that the 2‐D asymmetric reconnection theory [ Cassak and Shay , ] quantitatively describes the local reconnection rate at the dayside magnetopause in the global geometry for due southward IMF and no dipole tilt [ Borovsky et al , ; Ouellette et al , ; Komar and Cassak , ]. So we use v in, s = E / B s , with E=BsBmBs+Bmvout2δL, where δ / L is the aspect ratio of the diffusion region, assumed to be 0.1 for fast reconnection (even in the asymmetric case) [ Cassak and Shay , ; Malakit et al , ], the m subscript denotes the values measured just on the magnetospheric side of the magnetosheath, and the asymmetric outflow speed is vout2=BsBmμ0Bs+BmρsBm+ρmBs. Equations and of the present study are direct copies of equations (19) and (13) from Cassak and Shay [].…”
Section: Resultsmentioning
confidence: 99%
“…For the inflow speed, it has been shown that the 2‐D asymmetric reconnection theory [ Cassak and Shay , ] quantitatively describes the local reconnection rate at the dayside magnetopause in the global geometry for due southward IMF and no dipole tilt [ Borovsky et al , ; Ouellette et al , ; Komar and Cassak , ]. So we use v in, s = E / B s , with E=BsBmBs+Bmvout2δL, where δ / L is the aspect ratio of the diffusion region, assumed to be 0.1 for fast reconnection (even in the asymmetric case) [ Cassak and Shay , ; Malakit et al , ], the m subscript denotes the values measured just on the magnetospheric side of the magnetosheath, and the asymmetric outflow speed is vout2=BsBmμ0Bs+BmρsBm+ρmBs. Equations and of the present study are direct copies of equations (19) and (13) from Cassak and Shay [].…”
Section: Resultsmentioning
confidence: 99%
“…Observations suggest that ( δ / L ) eff is of order 0.1. Numerical simulations have also confirmed this scaling and demonstrated that ( δ / L ) eff ∼0.1; these include local magnetohydrodynamic (MHD) simulations with a localized resistivity (Birn et al, ), local two‐fluid (Cassak & Shay, ) and local particle‐in‐cell (PIC) (Malakit et al, ; Pritchett, ) simulations, global magnetospheric MHD simulations (Borovsky, ; Borovsky & Birn, ; Komar & Cassak, ; Ouellette et al, ; Zhang et al, ), and global Vlasov simulations (Hoilijoki et al, ). This scaling along with ( δ / L ) eff ∼0.1 was then employed to develop a quantitative model of the coupling between the solar wind and Earth's magnetosphere (Borovsky, ; Borovsky & Birn, ).…”
Section: Introductionmentioning
confidence: 88%
“…In section 4.4 we identified that B z was a causal parameter during southward IMF, that is, when below the threshold B z =0. Since we know that strongly negative values of B z correlate with higher reconnection rates at the dayside magnetopause (Komar & Cassak, ), we look at how this could relate to the generation of magnetospheric ULF waves.…”
Section: Physically Interpreting External Ulf Generation Mechanismsmentioning
confidence: 99%